1995
DOI: 10.1021/bi00033a006
|View full text |Cite
|
Sign up to set email alerts
|

The Two Monofunctional Domains of Octameric Formiminotransferase-Cyclodeaminase Exist as Dimers

Abstract: Formiminotransferase-cyclodeaminase is a bifunctional enzyme arranged as a circular tetramer of dimers that exhibits the ability to efficiently channel polyglutamylated folate between catalytic sites. Through deletion mutagenesis we demonstrate that each subunit consists of an N-terminal transferase active domain and a C-terminal deaminase active domain separated by a linker sequence of minimally eight residues. The full-length enzyme and both isolated domains have been expressed as C-terminally histidine-tagg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 28 publications
1
28
0
Order By: Relevance
“…Given that moonlighting functions can depend on differences in protein-protein interactions (48), it seems possible that running these opposing reactions concurrently is facilitated by FT joining/not joining a protein complex related to histidine degradation. In this connection, it is relevant that mammalian FT-CD is an octamer that can dissociate into two types of monofunctional dimers, and that while the FT and CD activities of the octamer function separately with monoglutamylated folates, polyglutamates are channeled from the FT to the CD active site (34,53). Analogous behavior of prokaryote FT oligomers, or perhaps FT-CD complexes, together with polyglutamate-mediated channeling between FT and CD reactions, could result in the functional partitioning, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Given that moonlighting functions can depend on differences in protein-protein interactions (48), it seems possible that running these opposing reactions concurrently is facilitated by FT joining/not joining a protein complex related to histidine degradation. In this connection, it is relevant that mammalian FT-CD is an octamer that can dissociate into two types of monofunctional dimers, and that while the FT and CD activities of the octamer function separately with monoglutamylated folates, polyglutamates are channeled from the FT to the CD active site (34,53). Analogous behavior of prokaryote FT oligomers, or perhaps FT-CD complexes, together with polyglutamate-mediated channeling between FT and CD reactions, could result in the functional partitioning, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Dissociation and renaturation studies of FTCD suggested that one dimeric interface is responsible for the transferase activity and the other for the cyclodeaminase activity (Findlay & MacKenzie, 1988). Further evidence supporting this ®nding was provided by deletion mutagenesis (Murley & MacKenzie, 1995). These studies showed that each subunit consists of a N-terminal transferase active domain and a C-terminal deaminase active domain which are separated by a short linker sequence.…”
Section: Introductionmentioning
confidence: 89%
“…Hexahistidine-tagged formiminotransferase domain was overexpressed using the pBKe-Cm1 expression vector in Escherichia coli strain BL21/DE3 and puri®ed to homogeneity as described previously (Murley & MacKenzie, 1995), omitting the last DEAE Sepharose column. The pooled fractions containing the FT domain were then dialyzed into 25 mM MOPS pH 8.2, 10 mM K 2 SO 4 pH 7.3, 35 mM -mercaptoethanol and 10%(v/v) glycerol, with the addition of 20 mM EDTA to remove any Ni 2+ which may have leached from the Ni-NTA column.…”
Section: Protein Puri®cation and Crystallizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The TM1560 gene of Thermotoga maritima encodes a formiminotetrahydrofolate cyclodeaminase (FTCD_CD, EC 4.3.1.4), with a molecular weight of 22,581 Da (residues 1-202) and a calculated isoelectric point of 5.0. 1 This enzyme is part of the folate metabolic pathway and catalyzes the cyclization of the formimino group of N 5 -formimidoyltetrahydrofolate, yielding N 5 ,N 10 -methenyltetrahydrofolate and ammonia 2 [ Fig. 1(A)].…”
mentioning
confidence: 99%